2009
DOI: 10.1603/029.102.0529
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Forage Pearl Millet Genotypes to Chinch Bug (Heteroptera: Blissidae) Feeding

Abstract: Chinch bug, Blissus leucopterus leucopterus (Say) (Heteroptera: Blissidae), is one of the most important insect pests on forage pearl millet, Pennisetum glaucum L. R. Br., production in the southeastern United States. Twenty-nine forage pearl millet genotypes were assessed for chinch bug resistance by using stunt and necrosis ratings in combination with quantitative measurements of chlorophyll content and leaf photosynthetic rate. Plant stunt and leaf sheath necrosis ratings, and chlorophyll content in flag le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Similar compensatory photosynthetic mechanisms have been observed in tolerant but not susceptible cultivars of the turf grass species Buchloë dactyloides (Heng-Moss et al 2006) and the forage crop pearl millet (Ni, Wilson & Buntin 2009) following exposure to phloem-feeding chinch bugs (Blissus occiduus). In the B. dactyloides-B.…”
Section: Insect Herbivory Impacts Primary Metabolic Processessupporting
confidence: 59%
See 1 more Smart Citation
“…Similar compensatory photosynthetic mechanisms have been observed in tolerant but not susceptible cultivars of the turf grass species Buchloë dactyloides (Heng-Moss et al 2006) and the forage crop pearl millet (Ni, Wilson & Buntin 2009) following exposure to phloem-feeding chinch bugs (Blissus occiduus). In the B. dactyloides-B.…”
Section: Insect Herbivory Impacts Primary Metabolic Processessupporting
confidence: 59%
“…Similar compensatory photosynthetic mechanisms have been observed in tolerant but not susceptible cultivars of the turf grass species Buchloë dactyloides (Heng‐Moss et al . 2006) and the forage crop pearl millet (Ni, Wilson & Buntin 2009) following exposure to phloem‐feeding chinch bugs ( Blissus occiduus ). In the B. dactyloides – B. occiduus interaction, susceptible lines accumulated carbohydrate in the leaves, exhibited reduced rates of CO 2 fixation, photosynthetic electron transport and the photochemical efficiencies of photosystem II (PSII) leading to the conclusion that insect attack led to end‐product inhibition of photosynthesis with impaired electron flow through PSII.…”
Section: Insect Herbivory Impacts Primary Metabolic Processesmentioning
confidence: 99%
“…Similar results were observed in Ni et al [25] wherein attacks by Blissus leucopterus significantly reduced the chlorophyll content and, consequently, the photosynthetic rate in certain forage millet genotypes under field conditions; those authors reported that such a reduction decreased the leaf area and, consequently, reduced the accumulated biomass. Similarly, Wang et al [26] observed reductions in chlorophyll content due to an attack by herbivores, which may negatively affect plants' photosynthetic capacities.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, according to Nabity et al [29], when the insects feed on the xylem or phloem, water transport, stomatal aperture, and sucrose transport are affected, thereby reducing photosynthesis in the remaining leaf tissue of the attacked plants. Reduction in chlorophyll content and consequent reduction in photosynthetic capability have been observed for other sucking insects [30, 31]. According to Welter [32], 50% of the studies that examined insect-plant interactions have reported a loss of photosynthetic capability in the plants.…”
Section: Resultsmentioning
confidence: 99%